ANALISIS DESKRIPTIF CHANNEL YOUTUBE SATU PERSEN EPISODE “KUNCI KOMUNIKASI EFEKTIF MENJADI ASERTIF” - Fatichatul Mukarromah; Sukma Ari Ragil Putri (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study aims to find out the impact of using YouTube social media for teenagers. Communication is a very important need and is needed in social interaction activities among Indonesian teenagers. The development of increasingly sophisticated technology does not hinder social relations to interact in all fields. This study uses descriptive qualitative methods, the data in this study are through interviews, observations, and documentation with the purposive sampling method. The results show that teenagers feel addicted and have a tendency to like to access social media rather than the real world. The content of the YouTube channel “Satu Persen - Indonesian Life School” in the episode “kunci komunikasi efektif: menjadi asertif (menyatakan perasaan dengan jujur)”, has made a difference for teenagers. The use of this content is proven in providing new understanding to the audience.